Relationship between Hospitalization and Parental Stress and Anxiety in the Children's Care Room, Batara Siang Hospital, Pangkajene Islands - Sufatmiaty, Sufatmiaty; Andi Asrina; Yusriani (Journal of Aafiyah Health Research (JAHR), 2022)
Background: Various things that can cause anxiety and stress in parents due to hospitalization of children include disease diagnosis, length of stay for children, parental knowledge, and care environment. Diagnosis of illness can cause psychological pressure on parents. When parents listen to information about the diagnosis of a child's illness and are required to be hospitalized, this triggers parents thinking that their child is seriously ill so that they will be more anxious and afraid which can cause stress. Listening to the doctor's decision about the diagnosis of their child's illness is a very stressful event for parents. Method:This research method is quantitative. To analyze the relationship between hospitalization of children and parental anxiety stress in the child care room at Batara Siang Pangkep Hospital in 2021. This research will be carried out at Batara Siang Hospital, Pangkajene Islands, on 75 pairs of child respondents and their parents. Results:Based on the results of statistical analysis using the Chi-Square test, p-value 0.155 > 0.05 and 0.089 > 0.05 mean that H0 is accepted, meaning that there is no relationship between the child's diagnosis of stress and parental anxiety. P-value 0.037 < 0.05 and 0.002 < 0.05 means that H0 is rejected, meaning that there is a relationship between the length of stay of children on stress and parental anxiety. P-value 0.073 > 0.05 and 0.117 > 0.05 means that H0 is accepted, meaning that there is no relationship between the environment and parental stress and anxiety. P-value 0.036 > 0.05 and 0.001 > 0.05 means that H0 is rejected, meaning that there is a relationship between knowledge of stress and parental anxiety. Conclusion: The most related factor with stress and anxiety of parents at Batara Siang Hospital Pangkajene Islands is knowledge with an Exp (B) value of 32,022.